2017
DOI: 10.1038/srep43523
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Diffusion-Weighted Imaging and Radiogenomic Network Analysis of Glioblastoma multiforme

Abstract: In the past, changes of the Apparent Diffusion Coefficient in glioblastoma multiforme have been shown to be related to specific genes and described as being associated with survival. The purpose of this study was to investigate diffusion imaging parameters in combination with genome-wide expression data in order to obtain a comprehensive characterisation of the transcriptomic changes indicated by diffusion imaging parameters. Diffusion-weighted imaging, molecular and clinical data were collected prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Jamjoom et al [ 59 ] found that lower min MD within enhancing tumour regions predicted shorted OS. Similar behaviour was observed in a study by Heiland et al [ 73 ] for mean MD. Conversely, the mean MD and values were found not predictive for OS in studies by Huber et al and Mohan et al [ 67 , 81 ] and, normalized for normal contralateral brain tissue, predictive for OS only in the univariate analysis performed by Zikou et al [ 47 ], but not in the multivariate one.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Jamjoom et al [ 59 ] found that lower min MD within enhancing tumour regions predicted shorted OS. Similar behaviour was observed in a study by Heiland et al [ 73 ] for mean MD. Conversely, the mean MD and values were found not predictive for OS in studies by Huber et al and Mohan et al [ 67 , 81 ] and, normalized for normal contralateral brain tissue, predictive for OS only in the univariate analysis performed by Zikou et al [ 47 ], but not in the multivariate one.…”
Section: Resultssupporting
confidence: 91%
“…Controversial results were also observed concerning FA. In a study by Heiland et al [ 73 ], a lower FA in the contrast-enhancing region was significantly associated with better OS. Moreover, Flores-Alvares et al [ 79 ] found significant association between the peritumoral oedema measurement of FA with OS.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, machine learning-based approaches including radiomics, radiogenomics, and so on, have drawn more and more attention and demonstrated the potential feasibility in lesion detection and classification, including but are not limited to prostate cancer, bladder cancer, glioblastoma, and non-small cell lung cancer (NSCLC) 18 , 33 – 35 . Radiogenomics referring to the combination of imaging and gene expression is reported to have the potential to give insight into tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…Heiland et al . 35 reported that DWI-derived parameter fractional anisotropy (FA) was strongly associated with EMT pathway activation by network analysis with diffusion data. Yamamoto et al .…”
Section: Discussionmentioning
confidence: 99%
“…The objective here is not to perform an exhaustive review, but rather highlight selected non-TCIA based studies by different groups that use different datasets and also investigate different cancer subtypes. Table V summarizes such approaches, namely for non-small cell lung cancer (NSCLC) [129], [130], [136], LGG [139], and GBM [126], [132], [133], [140], using different radiomic features stemming from multimodal MRI, PET, and CT image modalities.…”
Section: Non-tcia Cancer Radiogenomics Studiesmentioning
confidence: 99%